2020
DOI: 10.1101/2020.08.19.255844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic oxytocin-driven alternative splicing of CRFR2α induces anxiety

Abstract: Recently, oxytocin (OXT) has generated considerable interest as potential treatment for psychiatric disorders, including general anxiety disorder or autism spectrum disorder. Therefore, knowledge on the involved molecular processes downstream of OXT receptor (OXTR) activation is indispensable. We reveal that alternative splicing of corticotropin releasing factor receptor 2a (CRFR2a) parallels increased anxiety-like behavior following chronic OXT treatment, contrasting the well-known anxiolysis of acute OXT. In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Thus, we conclude that AVR-013 is a reliable and specific OTR antibody suited to study OTR levels in the rodent brain. In fact, this antibody has recently been used by other labs and validated using both peptide pre-incubation and knockdown approaches (34, 35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we conclude that AVR-013 is a reliable and specific OTR antibody suited to study OTR levels in the rodent brain. In fact, this antibody has recently been used by other labs and validated using both peptide pre-incubation and knockdown approaches (34, 35).…”
Section: Resultsmentioning
confidence: 99%
“…We found that OTR immunoreactivity was essentially absent in OTR KO mice, thus confirming the specificity of the antibody. In fact, although this is a new batch of the OTR antibody, other labs have also successfully used the same (34, 35) or older batches (59), albeit without confirming its specificity via animal OTR KO models. We used this antibody to investigate neuronal and astrocytic OTR expression and obtained results ( Figure 4 and 5 ) consistent with our data obtained via RNAScope ( Figure 5 and 6 ), again confirming the efficacy and specificity of the antibody.…”
Section: Discussionmentioning
confidence: 99%
“…OT has one known receptor, a G-coupled receptor that can have differing effects depending on which secondary messaging system it activates [65]. OT also has numerous interactions with hormones within the hypothalamic–pituitary–adrenal axis, including CRH and glucocorticoids [66,67]. Interactions between OT and the µ opioid system have been studied as well, both in the context of pregnancy in rats [68] and in social attention in primates [69].…”
Section: κ Opioids Oxytocin Corticotropin-releasing Hormone and Their...mentioning
confidence: 99%
“…For instance, acute OT negatively regulates transcription of the crf gene (Jurek et al, 2015). On the other hand, chronic OT treatment increases phosphorylation of myocyte enhancing factor 2A (MEF2A), a transcription factor that induces alternative splicing of the crf2a gene, leading to the formation of a soluble form sCRF2α (Winter et al, 2020). Indeed, studies have shown a positive correlation between sCRF2α and anxiety-like behaviour (Jurek & Meyer, 2020).…”
Section: Stress and Anxietymentioning
confidence: 99%